Takotsubo Syndrome and Oxidative Stress: Physiopathological Linkage and Future Perspectives - Alfredo Mauriello; Carmen Del Giudice; Gerardo Elia Del Vecchio; Adriana Correra; Anna Chiara Maratea; Martina Grieco; Arianna Amata; Vincenzo Quagliariello; Nicola Maurea; Riccardo Proietti; Antonio Giordano; Antonello D’Andrea; et al. (Antioxidants)
Takotsubo syndrome (TTS) is an acute coronary syndrome of unknown prevalence with a physiopathological mechanism that is not yet fully understood. The course is generally benign. Current therapeutic management is based on limited evidence. Oxidative stress seems to play a role in the pathogenesis of cardiovascular diseases, especially regarding the endothelial dysfunction underlying TTS. The present review aims to describe the pathophysiological mechanisms linking oxidative stress and TTS, explore the impact of oxidative stress on TTS, and evaluate the efficacy of anti-oxidative stress therapies on TTS.